Advancements in Nanoscale Chemical Analysis using Tip-Enhanced Raman Spectroscopy - Siiri Bienz; Chengcheng Xu; Yuanzhi Xia; Anushree Dutta; Renato Zenobi; Naresh Kumar (CHIMIA)
Tip-enhanced Raman spectroscopy (TERS) has established itself as a powerful tool in nanoscale chemical analysis, providing unprecedented spatial resolution with high molecular sensitivity and chemical specificity. TERS employs localized surface plasmon resonance at the apex of a sharp scanning probe microscopy tip to overcome the diffraction limit inherent in conventional Raman spectroscopy, achieving spatial resolutions down to the nanometer scale. In this article, we highlight major advancements in TERS over the past five years from our laboratory at ETH Zurich in the following key areas: heterogeneous catalysis, photovoltaic materials, biological membranes, and on-surface molecular assembly. Our recent studies demonstrate the unique capabilities of TERS for in situmonitoring of catalytic reactions, nanoscale mapping of phase behavior in biomembranes, and precise characterization of photovoltaic interfaces. Through these applications, we highlight the potential of TERS for addressing critical challenges across the chemical, biological, and materials sciences. This review serves as a guide for researchers aiming to harness TERS for label-free, non-destructive nanoanalysis to advance understanding of complex molecular materials and processes through ultrahigh sensitivity, specificity, and spatial resolution.